Urogynecology: Evidence-Based Clinical Practice - Moore, Kate. (Springer London : Imprint: Springer, 2006)
With the rising prevalence of urinary incontinence and prolapse in an aging population in the Western world, there is an increasing need for knowledge about this subject. Urogynecology: Evidence-Based Clinical Practice is written in easily understood language, giving the practical elements of urinary incontinence and prolapse. The book avoids the depths of research detail, common to the large texts, and summarizes practical patient management based upon available evidence and the author’s own clinical experience, indicating controversial areas where there is insufficient evidence. The book provides advice on how to make a rapid assessment and start conservative treatment for general practitioners, and provides information suitable for junior gynecology /female urology trainees. Current management options are described, so that consultant gynecologists with no previous formal urogynecological training would find this a useful quick practical update.